Business Modality Therapy in Improving Mother's Health during the Covid-19 Pandemic - Rohaedi, Slamet; Dharmansyah, Dhika; Fitriana, Lisna Anisa (Indonesian Journal of Community Development, 2021)
The COVID-19 pandemic has had various impacts on the entire family. For some families, this can mean making significant changes in their daily routine due to financial difficulties. The role of a mother to be economically empowered is very much needed. In addition, women also have the potential to become entrepreneurs to meet family needs and show their existence and optimize the potential of women. This activity aims to improve women's soft skills in entrepreneurship and online business. Implementation methods are using online learning through video conferences. The results that they can understand and motivate to build their own business. This business modality therapy is well implemented and effective in increasing productivity and improving mothers' health during the covid-19 pandemic.